Indigenous transport methods: Hormonal responses and physicochemical properties of lamb meat - MAK Azad; Sakib, MN; Murshed, HM; Hashem, MA; Ali, MS; Habib, M; Billah, MM (Meat Research, 2022)
The purpose of this study was to determine the effects of indigenous transport methods on hormonal responses and physico-chemical meat quality in lambs. The lambs (n=10) were exposed to different indigenous transport methods: NT (non-transport group), DT (3 h direct transport), WT (30-minute walking before 3 h direct transport), and WTWHJ (30-minute walking before 3h transport and afterwards 30-minute walking in human movement). Blood samples were collected via jugular venipuncture from TS and NT lambs. Indigenous transport methods significantly decreased the functions of T3 , T4 and TSH hormones compared to the non-transport group. On opposite, cortisol values were triggered by straight-cut journey and found decreased with the rest. Lambs upon exposure to indigenous transport methods showed elevated ultimate pH values than non-transport lambs. Both drip and cooking loss was significantly lower in indigenous transport protocols as compared to the control. The opposite trend was observed in case of water-holding capacity parameter. CIE L*, b* and a* values were significantly altered by indigenous transport methods. In conclusion, the present study indicated that indigenous transport methods may able to disturb the hormonal functions and also to produce poor grade lamb.